Evaluation of thrombolytic activity of three ethnomedicinal plants in bangladesh - Juthi, Tahmina Sultana; Kuddus, Md Ruhul; Uddin, Mohammad Zashim; Hassan, Md Abul; Rashid, Mohammad A (Bangladesh Journal of Botany, 2025)
The current study was designed to explore the thrombolytic activity of Allium cepa, Cinnamomum tamala and Ipomoea aquatica. All of them showed thrombolytic activity which was determined as part of a new probe of cardioprotective drugs from medicinal plants. It showed that the addition of 100 μl of streptokinase solution as a positive thrombolytic control (30000 I.U.) to blood clots with 90 min incubation at 370C showed 68.79 % of clot lysis. In contrast, distilled water considered as negative non-thrombolytic control revealed insignificant level of clot lysis activity. All the tested extracts showed mild to moderate thrombolytic activity. Among these, C. tamala leaf extract showed highest (58.99 %) thrombolytic activity for clot lysis. Based on the outcomes, it is perceived that all the three plants revealed thrombolytic activity which is needed for further analysis to validate the active components of these extracts. Bangladesh J. Bot. 54(3): 619-622, 2025 (September)